Preparation and Properties Study of Cementitious Grouts Containing Crumb Rubber - Wei Yuan (MDPI AG, 2021)
This article aims to improve the toughness of pre-packaged grouts (PPG) by incorporating crumb rubber. The mechanism for toughness of PPG with crumb rubber was analyzed based on the uniaxial compression model. Crumb rubber with surfaces treated by different methods (NaOH solutions or microwave treatment) was observed by scanning electron microscopy (SEM). The effects of mesh sizes, amounts, surface-treated methods of crumb rubber, and mixing procedures on the PPG’s mechanical strength and rheological properties were investigated. The results showed that, firstly, the addition of crumb rubber improves the PPG’s toughness, while its mechanical strength is reduced. Adding NaOH solutions or microwave-treated crumb rubber into PPG can weaken the negative effects of crumb rubber on the PPG’s mechanical strength; however, this function is limited. Secondly, the crumb rubber grouts’ rheological properties can be fully exploited by increasing the stirring rate and time so that the fluidity of crumb rubber grouts is improved, which fulfils the characteristics of no bleeding and micro-expansion. Finally, the optimal formula and mixing technique of crumb rubber grouts were proposed in this paper.The results of this paper can provide a significant reference for the application of scrap tires.